Plan de marketing para el posicionamiento del yogurt kibutz de la empresa de lácteos San Antonio de la provincia de Manabí - Lara Zambrano, Erika (2022)
The present study included the proposal of a marketing plan for the positioning of the Kibutz yogurt of the San Antonio dairy company in the north of Manabí, whose development was carried out in three methodological phases, corresponding to the specific objectives of the research. In the first place, the current situation of the dairy company was diagnosed, for which it was pertinent to carry out an analysis of the internal and external factors that affect its positioning, through an interview with the manager, an analysis of the macro political, economic environment, social and technological, and a study of the five forces of Porter, whose results were synthesized and exposed in the SWOT matrix. The second phase corresponds to the development of a market study to find out the potential demand for Kibutz yogurt, through the application of an acceptance survey, market segmentation, and the determination of the potential supply and demand of the product. Finally, in the third phase the strategy proposal was developed, whose objectives and directions were elaborated based on the four P's of marketing, in addition to the advertising and promotion plan, as well as the due execution budget. The main results show that the company has skills in terms of knowledge of marketing techniques and advertising tools, in addition to a low level of positioning in the market in the northern area of Manabí, which is why the relevant resulting strategic proposal of study and application.